Evaluation of the URiSCAN Super Cassette ACR Semiquantitative Urine Dipstick for Microalbuminuria Screening - Cho, Min‐Chul (J Clin Lab Anal, 2014)
BACKGROUND: Microalbuminuria tests are used as screening tools for diseases, such as diabetic nephropathy, cardiovascular disease, and hypertension. The purpose of this study was to evaluate the utility of a newly introduced semiquantitative urine dipstick, URiSCAN Super cassette ACR (URiSuper‐ACR [where ACR is albumin/creatinine ratio]; YD Diagnostics Corp., Korea), as a screening tool for microalbuminuria. METHODS: Albumin and creatinine levels in randomly selected spot urine samples of 1,040 patients were semiquantitatively measured using URiSuper‐ACR. Results using URiSuper‐ACR system were compared to measurements obtained by quantitative analyzer. We also calculated diagnostic sensitivity, specificity, precision, linearity, and categorical concordance rates for the diagnosis of microalbumiuria using this system. Furthermore, we performed interference tests using standard controls to evaluate possible influence of various factors. RESULTS: URiSuper‐ACR test showed 88.8% and 86.3% sensitivity and 90.1% and 93.8% specificity for albumin concentration and ACR, respectively. It also showed 91.1% and 92.6% positive predictive values and 87.6% and 88.5% negative predictive values, respectively. The concordance rate between URiSuper‐ACR and quantitative method for albumin and creatinine concentration within the same category were 78.4% and 67.1%, respectively, and for the ±1 category were 98.8% and 99.5%, respectively. For ACR, an 80.0% concordance rate was seen within the same category. The within‐run coefficients of variation (CVs) were 3.0∼15.4% and 5.2∼23.5% for albumin and creatinine, respectively, showing good linearity. In interference tests, no interference was observed except for cases with high specific gravity. CONCLUSIONS: URiSuper‐ACR showed good diagnostic performance for the detection of microalbuminuria and may be a useful screening test in clinical laboratories.